INVESTIGATION OF THE SOURCES OF FOUNDRIES AND SCALES OF POLLUTION OF THE ENVIRONMENT WITH HARMFUL EMISSIONS - A. M. Lazarenkov; S. A. Horeva (Литьë и металлургия, 2008)
The investigation of sources of environmental pollution with pollutant emissions is carried out. The investigations were carried out on all kinds of pollutant emissions taking into account the applied technological processes.